2017
DOI: 10.3390/ijms18071402
|View full text |Cite|
|
Sign up to set email alerts
|

Capsaicin-Sensitive Sensory Nerves Are Necessary for the Protective Effect of Ghrelin in Cerulein-Induced Acute Pancreatitis in Rats

Abstract: Ghrelin was shown to exhibit protective and therapeutic effect in the gut. Aim of the study was to investigate the role of sensory nerves (SN) in the protective effect of ghrelin in acute pancreatitis (AP). Studies were performed on male Wistar rats or isolated pancreatic acinar cells. After capsaicin deactivation of sensory nerves (CDSN) or treatment with saline, rats were pretreated intraperitoneally with ghrelin or saline. In those rats, AP was induced by cerulein or pancreases were used for isolation of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 98 publications
1
19
0
Order By: Relevance
“…Clinical practice and research studies indicate that the pathological processes of pancreatitis and its complications are the two major factors underlying SAP-associated morbidity and mortality ( Zerem, 2014 ; Shah et al, 2018 ). The two most common disease processes are inflammation ( Bonior et al, 2017 ) and oxidative stress ( Deng et al, 2016 ), whereas intestinal dysfunction is a frequent extra-pancreatic complication ( Zhang et al, 2015 ). Effective treatment options are lacking resulting in patient suffering and high treatment costs.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical practice and research studies indicate that the pathological processes of pancreatitis and its complications are the two major factors underlying SAP-associated morbidity and mortality ( Zerem, 2014 ; Shah et al, 2018 ). The two most common disease processes are inflammation ( Bonior et al, 2017 ) and oxidative stress ( Deng et al, 2016 ), whereas intestinal dysfunction is a frequent extra-pancreatic complication ( Zhang et al, 2015 ). Effective treatment options are lacking resulting in patient suffering and high treatment costs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that ghrelin—an alternative product of post-translational processing of preproghrelin—exhibited a protective effect in gastrointestinal mucosa against damage caused by harmful factors [ 46 , 47 , 48 , 49 , 50 ], and potentially inhibited the development of acute pancreatitis [ 51 , 52 , 53 ]. Ghrelin also had a therapeutic effect in the gastrointestinal tract [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because TNF‐α plays a detrimental role in OA development and chondrocyte degeneration (44) and ghrelin antagonized TNF‐α in several conditions (45), we determined the role of ghrelin in TNF‐α‐mediated chondrocyte catabolism. Human articular chondrocytes were isolated and stimulated with TNF‐α (10 ng/ml) for 12 h with or without simultaneous administration of ghrelin (50 ng/ml).…”
Section: Resultsmentioning
confidence: 99%